New Records of Squamates from the Upper Miocene of South America - Albino, Adriana Maria (2013)
The Cerro Azul Formation of Argentina has yielded one of the highest diversities of squamate reptiles for the upper Miocene of South America including tupinambine teiids (Tupinambis sp.), ‘‘colubrids,’’ and viperids. Here, we describe new remains of Tupinambis sp. and ‘‘Colubridae’’ from this Formation as well as the first records of teiine teiids and boid snakes. The teiine represents the oldest record of this subfamily in South America. The squamate assemblage of the Cerro Azul Formation is consistent with the mammalian fauna in supporting the interpretation of a Chacoan-type palaeoenvironment for the upper Miocene of Central Argentina.